Bile acids drive the newborn’s gut microbiota maturation - N. van Best (Nature Portfolio, 2020)
Early postnatal colonization has been described to be critical for the long-term microbiota composition and health. Here, via multi-omics approach, the authors investigate the impact of the developing host hepatic metabolism on the murine intestinal microbiota composition with comparative analysis at immediate postnatal period, early infancy and weaning and adulthood.